Phytoplankton Diversity of Cauvery River in Erode, Tamil Nadu - S. Uthirasamy; T. Chitra; S. Ravichandiran; T. Kavitha (Recent Research Advances in Biology Vol. 7, 2021)
The Cauvery River is the main water source for many places in Tamil Nadu. It is highly polluted in Erode district due to improper management of textile effluents. This study was carried out to analyse the phytoplankton diversity of the Cauvery River in Erode district, Tamil Nadu, India. Planktons are the basic food source of the aquatic ecosystem. Phytoplankton diversity is one of the most important ecological indicators for the assessment of water quality. This study was designed to analyse the phytoplankton during the period of July 2017 to June 2018 and the results were recorded periodically. The results revealed that the diversity of Phytoplankton is good indicators for the river ecosystem and influenced by the quality of river water.